The Cost-Effectiveness of Human Immunodeficiency Virus Testing and Treatment Engagement Initiatives in British Columbia, Canada: 2011–2013. (26th September 2017) - Nosyk, Bohdan; Min, Jeong E; Krebs, Emanuel; Zang, Xiao; Compton, Miranda; Gustafson, Reka; Barrios, Rolando; Montaner, Julio S G; ,
Abstract : We used a dynamic human immunodeficiency virus (HIV) transmission model to determine the cost-effectiveness of HIV care interventions in British Columbia, Canada, in 2011–2013. HIV testing and treatment initiation interventions were cost-effective, while the treatment retention intervention was not. Abstract: Background: Recognition of the secondary preventive benefits of antiretroviral therapy (ART) has mobilized global efforts to "seek, test, treat, and retain" people living with human immunodeficiency virus [HIV]/AIDS (PLHIV) in HIV care. We aimed to determine the cost-effectiveness of a set of HIV testing and treatment engagement interventions initiated in British Columbia, Canada, in 2011–2013. Methods: Using a previously validated dynamic HIV transmission model, linked individual-level health administrative data for PLHIV, and aggregate-level HIV testing data, we estimated the cost-effectiveness of primary care testing (hospital, emergency department [ED], outpatient), ART initiation, and ART retention initiatives vs a counterfactual scenario that approximated the status quo. HIV incidence, mortality, costs (in 2015$CDN), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios were estimated. Analyses were executed over 5- to 25-year time horizons from a government-payer perspective. Results: ED testing was the best value at $30216 per QALY gained and had the greatest impact on incidence and mortality among PLHIV, while ART initiation provided the greatest QALY gains. The ART retention initiative was not cost-effective. Delivered in combination at the observed scale and sustained throughout the study period, we estimated a 12.8% reduction in cumulative HIV incidence and a 4.7% reduction in deaths among PLHIV at $55258 per QALY gained. Results were most sensitive to uncertainty in the number of undiagnosed PLHIV. Conclusions: HIV testing and ART initiation interventions were cost-effective, while the ART retention intervention was not. Developing strategies to reengage PLHIV lost to care is a priority moving forward.